2022
DOI: 10.3390/nu14142882
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Intake, C-Reactive Protein, and Muscle Mass in Adolescents

Abstract: Background: Adult studies have suggested that magnesium intake may regulate C-reactive protein (CRP) and muscle mass, known risk factors for cardiometabolic diseases. Given the large deficiencies in magnesium intake in adolescents, we aimed to investigate sex and race differences in dietary magnesium intake and test the hypothesis that lower magnesium intake is associated with higher CRP and lower muscle mass. Methods: A total of 766 black and white adolescents, 14 to 18 years old (51% black; 50% female) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Our findings elucidated a protective role of dietary Mg in maintaining muscle mass among hypertensive patients, which is in line with previous studies conducted in the general population [ 18 20 , 33 ]. A systemic review about minerals and muscle mass suggested that Mg may regulate health through muscle activity [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings elucidated a protective role of dietary Mg in maintaining muscle mass among hypertensive patients, which is in line with previous studies conducted in the general population [ 18 20 , 33 ]. A systemic review about minerals and muscle mass suggested that Mg may regulate health through muscle activity [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…A systemic review about minerals and muscle mass suggested that Mg may regulate health through muscle activity [ 20 ]. Moreover, a study including 766 adolescents also found that lower Mg intake was associated with lower muscle mass [ 33 ]. Inadequate Mg intake is common in the U.S. population.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of age, the absorption and utilization ability of magnesium may gradually decline, and at the same time, due to the weakening of metabolic function, blood sugar control may be more difficult. Some studies 14 , 15 suggested that hyperglycemia in T2DM increases the glomerular filtration rate, leading to inadequate magnesium reabsorption in renal tubules, resulting in elevated urinary magnesium excretion and decreased serum magnesium concentration. Furthermore, a study 16 in pre-diabetes indicated that increased renal magnesium consumption due to uncontrolled diabetes may contribute to low serum magnesium levels.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between magnesium intake and serum inflammatory marker levels and HOMA-IR, it seems that magnesium intake is significantly inversely related to hs-CRP, IL-6, fibrinogen, and HOMA-IR, and serum magnesium level is inversely related to hs-CRP and HOMA-IR [ 64 ]. Another meta-analysis concluded that there is an inverse relationship between dietary magnesium intake and serum magnesium concentrations with the risk of total cardiovascular events [ 65 ]. It is abundantly clear that magnesium deficiency maintains both hyperinflammation in acute inflammatory processes and low-grade inflammation in chronic diseases [ 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%